Predicting preschool children's digital play addiction tendency during Covid-19 pandemic: Regarding the mother-child relationship, and child- and family-related factors - Ilvan, Tugba Emiroglu; Ceylan, Remziye (SPRINGER, 2023)
Previous research about children's digital play has predominantly focused on parental perspectives and parental mediation strategies. Although research on the effects of digital play on young children's development is plentiful, there is little evidence on young children's digital play addiction tendency. Herein, preschool children's digital play addiction tendency, and the mother-child relationship perceived by mothers, examining child- and family-related factors were explored. The present study also aimed to contribute to the current research pertaining to preschool-aged children's digital play addiction tendency through an examination of the mother-child relationship, and child- and family-related factors as potential predictors of children's digital play addiction tendency. A sample of 450 mothers of children between 4 and 6 years filled out two measures that identify the mother-child relationship and children's digital play addiction tendency. Correlational analyses revealed that in general, the mother-child relationship was significantly associated with children's digital play addiction tendency. Significant differences were evident in the relationship between numerous child- and family-related factors, and children's digital play addiction tendency, as well as the mother-child relationship. Hierarchical regression analyses indicated that a negative mother-child relationship, the children's digital play usage, and the mothers' digital device usage predicted the children's digital play addiction tendency.
Keywords: Digital play addiction tendency; Mother-child relationship; Preschool children; Gender; Digital play usage; ONLINE GAME ADDICTION; PARENTAL MEDIATION; VIDEO GAMES; SCREEN TIME; DEVICE USE; INTERNET; SCHOOL; ATTITUDES; IMPACT; SKILLS; Education & Educational Research